2016
DOI: 10.1039/c5ob02408k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, analysis and biological evaluation of novel indolquinonecryptolepine analogues as potential anti-tumour agents

Abstract: A small library of cryptolepine analogues were synthesised incorporating halogens and/or nitrogen containing side chains to optimise their interaction with the sugar-phosphate backbone of DNA to give improved binding, interfering with topoisomerase II hence enhancing cytotoxicity. Cell viability, DNA binding and Topoisomerase II inhibition is discussed for these compounds. Fluorescence microscopy was used to investigate the uptake of the synthesised cryptolepines into the nucleus. We report the synthesis and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Hence, a whole variety of bioisosterisms and salt forms of them were synthesized to explore their activities against plant pathogenic fungi. 23 From the activity data results, we found that the salt form c1 of cryptolepine exhibited an improved activity with an EC 50 of 0.041 μg/mL against B. cinerea. However, the antifungal activity of cryptolepine would become worse when the methyl at C5 was lacking.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Hence, a whole variety of bioisosterisms and salt forms of them were synthesized to explore their activities against plant pathogenic fungi. 23 From the activity data results, we found that the salt form c1 of cryptolepine exhibited an improved activity with an EC 50 of 0.041 μg/mL against B. cinerea. However, the antifungal activity of cryptolepine would become worse when the methyl at C5 was lacking.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
“…According to the previous work reported by Ning et al, cryptolepine derivatives were prepared by replacing the nitrogen atom at position 10 with oxygen or sulfur to search for antimicrobial agents. Hence, a whole variety of bioisosterisms and salt forms of them were synthesized to explore their activities against plant pathogenic fungi . From the activity data results, we found that the salt form c1 of cryptolepine exhibited an improved activity with an EC 50 of 0.041 μg/mL against B.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbolines, usually known as pyrido[ x , y-b ]indoles, have emerged as important N-heterocycles with a broad spectrum of biological activities, which could be divided into α-, β-, γ- and δ-carbolines according to the position of the N atom. 1,2 Among these various types of carbolines, δ-carbolines are identified as privileged units in plenty of natural alkaloids, pharmaceuticals, and functional materials (Scheme 1a). 2 For example, CzBPDCb was used as an electron transport unit bipolar host material for blue phosphorescent organic light emitting didoes, 2 a N 5 -ω-cyclohexylpentyl- N 1 -methyl-δ-carbolinium displayed antibacterial and antifungal activities, 2 b PIQ could serve as a potential structure-selective G-quadruplex binding molecule, 2 c natural alkaloid Jusbetonin was isolated from Justicia betonica , 2 d and SYUIQ-5 is a potential anticancer therapeutic.…”
Section: Introductionmentioning
confidence: 99%
“…The search for new effective methods for the synthesis of quindoline as a cryptolepine precursor, its structural analogs and δ‐carbolines is caused by the high relevance of problems of malaria and tuberculosis control ,,…”
Section: Introductionmentioning
confidence: 99%